At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
44-2x=x-10
subtract 44 from both sides
-2x= x-54
subtract x from both sides
-3x= -54
divide by -3
x= 18
square root of 18= 4.24
in radical form 3 square root of 2
hope this helps
sqrt(44 - 2x) = x - 10
44 - 2x = (x - 10)^2 = x^2 - 20x +100
0 = 1x^2 - 18x + 66
yikes! quadratic formula
ax^2 + bx + c = 0
a = 1
b = -18
c = 66
x = [-b ± sqrt(b^2 - 4ac)]/(2a)
x = [18 ± sqrt((-18)^2 - 4(1)(66))]/(2(1))
x = 12.873 or 5.127
44 - 2x = (x - 10)^2 = x^2 - 20x +100
0 = 1x^2 - 18x + 66
yikes! quadratic formula
ax^2 + bx + c = 0
a = 1
b = -18
c = 66
x = [-b ± sqrt(b^2 - 4ac)]/(2a)
x = [18 ± sqrt((-18)^2 - 4(1)(66))]/(2(1))
x = 12.873 or 5.127
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.